Consumers' Expectations on Transparency of Sustainable Food Chains - Pozelli Sabio, Renata; Spers, Eduardo Eugênio (Frontiers in Sustainable Food Systems, 2022)
The search for food products from sustainable chains has increased in the past years, motivated by consumers' interest in reducing the negative environmental, economic, and health impacts of their food choices. However, it is not yet clear whether transparency expectations of sustainable food chains influence in consumers' perception of this food products. The literature shows that there are gaps in the growth of sustainable product consumption is the transparency of production and the provision of more information to consumers. In this paper, we aimed to better understand what is the role of transparency expectations and how they influence consumers' decision to consume sustainable food products. Based on scales already validated in the literature, a theoretical model with nine hypotheses was proposed. A questionnaire was structured and empirically tested through a survey with 136 consumers of food from alternative networks. Six hypotheses were validated. Three segments of consumers target were identified from an exploratory factor analysis and cluster. Based on the results some marketing actions were suggested for the participants of alternative food networks. Other studies may validate the model proposed here.